Audiencia y Consumo Cultural en Chile. ¿Tópico o Justificación de un Modelo de Democratización de la Cultura: 1990-2005? - Antoine, Cristian (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
At the beginnings of the 90’s decade, concepts such as "culture consumption", "formation of public" and "audience development” didn’t exist as arguments in order to justify the newly born culture policies in Chile and its ruling agency, the “Culture and Arts Council”. A decade and half later, the three concepts mentioned before are fully installed into official speech. This happen simultaneously with the development of new assessing techniques that made possible a "measurement" of culture consumption in Chile. This review explores how the public policies in culture were born in Chile and how were they tied with the first attempts to study and diagnose this field of activity. It also ponders the importance of technical qualification in the process of formulation and later evaluation of the efficacy of public policies in culture